Efficacy of intravenous propafenone in converting atrial fibrillation and flutter in sinus rhythm [Atriyal fibrilasyon ve flatterin sinus ritmine cevrilmesinde intravenoz propafenonun etkinligi] - (:unkn) unknown (My University, 1997)
Propafenone has been claimed to be effective in converting atrial fibrillation and flutter to sinus rhythm. However, controlled clinical trials have reported conflicting results, and data about the safety of propafenone in the setting of heart failure are lacking. The aim of the present study was to evaluate the efficacy and safety of intravenous propafenone in converting atrial fibrillation and flutter to sinus rhythm, in patients with and without heart failure. Sixty patients with acute (<72 h) or chronic (>72 h) atrial fibrillation or flutter were included in a randomized, placebo-controlled, conditional cross-over study. Twenty-eight patients had heart failure of whom 12 were in NYHA class III and IV. Patients received intravenous propafenone (2 mg/kg in 10 min) and placebo subsequently with a 1-h interval if sinus rhythm was not achieved. The patients' rhythm was continuously monitored for 1 h and a 12-lead electrocardiogram, a 1-min continuous rhythm strip and vital signs were recorded at baseline and 15, 30, 45 and 60 min after the administration of each drug. Twenty of the 59 patients (34%) treated with propafenone converted to sinus rhythm while only 4 of the 50 patients (8%) treated with placebo converted (p < 0.001). Propafenone was more effective in patients with acute atrial fibrillation with a success rate of 64.5% (20/31). The mean time to conversion was 15 ± 9 min. The conversion rate with propafenone was not significantly different from placebo in patients with atrial flutter and chronic atrial fibrillation. While none of the 12 patients with NYHA Class III or IV heart failure and chronic atrial fibrillation responded to propafenone, 4 of the 5 patients (80%) with NYHA Class II heart failure and acute atrial fibrillation converted to sinus rhythm. Propafenone significantly decreased (p < 0.0005 vs placebo) mean ventricular rate in nonresponders with baseline heart rate of more than 100 beats/min. No clinically significant adverse effect occurred. We conclude that (1) intravenous propafenone treatment is effective for converting acute atrial fibrillation, however, it seems unlikely to be beneficial in atrial flutter and in chronic atrial fibrillation, (2) propafenone decreases ventricular rate in nonresponders, (3) single-dose propafenone is relatively safe even in moderate to severe heart failure.